1999
DOI: 10.1038/sj.onc.1202950
|View full text |Cite
|
Sign up to set email alerts
|

γ-heregulin is the product of a chromosomal translocation fusing the DOC4 and HGL/NRG1 genes in the MDA-MB-175 breast cancer cell line

Abstract: g-heregulin is a recently described novel isoform of the heregulin/neuregulin class of EGF-like ligands that bind to and activate receptors of the ErbB family. Deregulated signaling through the heregulin-ErbB pathway is thought to be implicated in the development of a subset of human breast cancers. g-heregulin has been found to be expressed in the culture supernatant of MDA-MB-175, a breast carcinoma cell line. g-heregulin is characterized by the presence of a large N-terminal peptide extension that is not fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 11 publications
2
49
0
Order By: Relevance
“…Our results show that the t(8;11)(p12;q13) translocation is not present in a large series of Spanish women with breast cancer and confirm previous reports that suggest that this translocation is a particularity of the MDA-MB-175 cell line and not a recurrent event (Wang et al, 1999;Adélaïde et al, 2000) indicating that g-heregulin is not relevant in the development of breast cancer.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Our results show that the t(8;11)(p12;q13) translocation is not present in a large series of Spanish women with breast cancer and confirm previous reports that suggest that this translocation is a particularity of the MDA-MB-175 cell line and not a recurrent event (Wang et al, 1999;Adélaïde et al, 2000) indicating that g-heregulin is not relevant in the development of breast cancer.…”
supporting
confidence: 89%
“…Moreover, NRG-1 synthesised by the mesenchyme has been implicated in mammary development (Carraway et al, 1997), and it has been demonstrated that NRG-1 induces proliferation or differentiation of various mammary tumour cell lines, initiates programmed cell death and induces cell differentiation in breast tumours (Ram et al, 1995;Weinstein et al, 1998;Le et al, 2000). Recently, it has been identified in MDA-MB-175, a breast carcinoma cell line that shows elevated levels of HER-2 (Lewis et al, 1993), a translocation between chromosomes 8p12-21 and 11q13 that leads to the fusion of NRG-1 and DOC4 genes (Schaefer et al, 1997;Liu et al, 1999;Wang et al, 1999;Adélaïde et al, 2000). This translocation generates a new chimeric transcript that codes for a new isoform of the neuregulin family, denominated g-heregulin (g-HRG), that acts as an autocrine growth factor in the breast cancer cell line MDA-MB-175 (Schaefer et al, 1997).…”
mentioning
confidence: 99%
“…MDA-MB-175 has a translocation of 8p12 at NRG1 that creates a fusion with the DOC4 gene on chromosome 11 (Wang et al, 1999;Liu et al, 1999;Adelaide et al, 2003). The fragment containing the junction is amplified (Figure 3).…”
Section: Mda-mb-175mentioning
confidence: 99%
“…NRG1 encodes the heregulins/neuregulin 1 family of ligands, which bind to ErbB2, 3 and 4. Our working hypothesis is that the translocations result in aberrant expression of normal or modified heregulins, which act in an autocrine loop on the cancer cells, as in at least one of the cell lines, MDA-MB-175, the translocation results in fusion of NRG1 and secretion of a fusion protein with soluble heregulin-like activity (Schaefer et al, 1997;Liu et al, 1999;Wang et al, 1999). We have subsequently shown that breakpoints in NRG1 are present in about 6% of uncultured breast tumours (Huang et al, 2004 also supported by Prentice et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…For other amplification regions, such as the 8p12 and 20q13 regions, and for deletions, the identity of the cancer genes remains uncertain. The characterisation of translocations has provided additional cancer gene candidates, such as FHIT (Popovici et al, 2002), NTRK3 and ETV6 (Tognon et al, 2002; our unpublished observations), BCAS (Bärlund et al, 2002) and NRG1 (Wang et al, 1999;Adélaïde et al, 2003;Huang et al, 2004) genes. Given the number of recurrent chromosomal breaks observed in breast cancer (http://cgap.nci.nih.gov/Chromosomes/ RecurrentAberrations), this line of research might become more fruitful than the search for deletions through loss of heterozygosity data, which has been rather disappointing (Devilee et al, 2001).…”
mentioning
confidence: 80%